Analysis of the scientific literature on mobile applications for language teaching - Vanessa Guadalupe Félix Aviña; Vilma Zoraida Rodríguez Melchor (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales, 2023)
Mobile language learning apps have become popu-lar due to their accessibility, flexibility, and ability to provide personalized learning experiences. This article explores the development of mobile applica-tions for language learning based on the most rele-vant publications of the Web of Science in the last ten years. Do density maps were created through the VOSviewer program to identify countries, institutions, and the most relevant concepts on the object of study. The results show the relevance of emerging technologies such as artificial intelligence, data analytics and augmented reality for the design of models, systems and programs for language learning.